EVALUASI PELAKSANAAN KEGIATAN MANAJEMEN RISIKO MENGGUNAKAN COSO: ENTERPRISE RISK MANAGEMENT-INTEGRATED FRAMEWORK STUDI KASUS: RUMAH SAKIT XYZ - , ELLINA PUSPITA SARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Every organizations facing various risks. Risk is the possibility that something bad or unpleasant (such as an injury or a loss) will happen. Organizations tend to avoid risks because they can give bad impact for organizations if they are not able to manage their risks well. To minimize those risks, organizations have to conduct good risk management by identifying, assessing and deciding respons for those risks. Enterprise risk management is a process, effected by an entity's board of directors, management, and other personnel, applied in strategy setting and across the enterprise, designed to identify potential events that may affect the entity, and manage risk to be within its risk appetite, to provide reasonable assurance regarding the achievement of entity objectives. COSO: Enterprise Risk Management is a framework released by COSO as a guidance which is able to help organizations in managing their risks. This framework has four vertical category: strategic, operation, reporting and compliance also has eight horizontal components consists of internal environment, objective setting, events identificarion, risk assessment, risk respond, control activity, information and communication and monitoring. This research is conducted by case study in Rumah Sakit XYZ to assessing how good Rumah Sakit XYZ manage their risks using COSO: Enterprise Risk Management-Integrated Framework. Result from this research shows that Rumah Sakit XYS has not conducted good risk management yet because they do not have risk management activities formally and well coordinated. The components in COSO framework also not conducted all yet so they need to considering to start risk management formally.